EFFECT OF ORAL CURCUMIN ADMINISTRATION ON NMDA RECEPTOR EXPRESSION AND RETINAL GANGLION CELL DENSITY: Oral Presentation - Experimental Study - Ophthalmologist - SALMAH ALAYDRUS; RISKI PRIHATNINGTIAS; ARNILA NOVITASARI; HERMAWAN ISTIADI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : To prove the effect of oral curcumin on NMDA receptor expression and retinal ganglion cell density. Methods : Wistar rats model of traumatic optic neuropathy were divided into 2 groups. The treatment group was given oral curcumin 150mg/kgBW/24 hours for 14 days 1 hour after trauma. NMDA receptor expression was examined by IHC staining and retinal ganglion cell density was examined by HE staining. Data were collected and analyzed. Results : NMDA expression was found to be significantly lower in the treatment group compared to the control group (p = 0.046). The mean of ganglion density in the control and treatment group was 12.88 ± 2.44 and 17.92 ± 6.95, respectively. The treatment group had a significantly higher ganglion density (p = 0.043). There was a significant relationship between NMDA receptor expression and retinal ganglion density (p = 0.043, r = -0.591). Conclusion : Curcumin can suppress the expression of NMDA receptors to maintain retinal ganglion density in rat models of optic neuropathy